Liquid chromatography mass spectrometry‐based O‐glycomics to evaluate glycosylation alterations in gastric cancer. Issue 2 (21st September 2015) - He, Yun; Xie, Qin; Wang, Yanping; Liang, Yong; Xu, Xiukun; Li, Yong; Miao, Jinsheng; Chen, Zijun; Li, Yunsen
Abstract : Purpose: Gastric cancer is the fourth most common malignant cancer worldwide. Important for tumorigenesis and progression, aberrant glycosylation occurs frequently in cancers. We investigated the differences in O‐glycosylation in the serum of 157 gastric cancer patients (GC) and 144 healthy donors. Experimental design: We used the method of labeling O‐glycans (released from proteins) with 1‐phenyl‐3‐methyl‐5‐pyrazolone followed by LC‐MS analysis. Analyzing the LC‐MS data by partial least squares discriminant and unpaired Student t test, combined with the structural information of O‐glycans from LC‐MS/MS in positive mode. Results: The expression level of core1, core2, ST antigen, and core2 complex O‐glycans ( m/z 733.33, m/z 809.42) were increased significantly ( p < 0.0001), whereas m/z 529.75 and diST‐antigen were decreased in the serum of GC compared with controls ( p < 0.001). In addition, there were significant correlations between the abundance of the O‐glycans and glycoproteins (MUC1, CEA) in the serum of GC. Conclusion and clinical relevance: Glycomics approaches identified multiple candidate antigens for patients with GC. The O‐glycan structures are increased in the serum of GC, they may be candidates for carbohydrate tumor markers.